A new species and ten new records of bdelloid rotifers from Korea - Song, Min Ok; Min, Gi-Sik (Zootaxa, 2015)
We conducted a taxonomic study of bdelloid rotifers collected from various terrestrial habitats, such as mosses, lichens, mushrooms on tree trunks, and leaf litter, at six different locations in Korea. The study yielded 10 new Korean records and a new species, Bradyscela hoonsooi n. sp. Among the 10 new Korean records, nine species are new to Asia, and seven of these are rare species with poorly known distributions. Our study is the first to record Habrotrocha fuscochlaena De Koning outside its type locality. Macrotrachela sonorensis Örstan and Habrotrocha acornis Murray have previously been reported from only two countries. Habrotrocha longula Bryce and Habrotrocha visa Donner are recorded outside Europe for the first time. Habrotrocha flaviformis De Koning has previously been reported from Europe, Brazil and New Zealand. Finally, Philodina grandis Milne has been reported from Eastern and Southern Africa and New Zealand before the present study. Here, we provide a description of the new species and discuss the taxonomy and distribution of the seven rare species.